The How of Happiness and Wellbeing - Bansal, Rahul (Indian Journal of Community Health, 2019)
The concept of happiness is unique to an individual. Everybody gets happy for different reasons. There is a large body of research on happiness and there are many well written books on happiness by internationally known psychologists and other experts. Though everybody is seeking happiness in his/her own way very few people seem to be genuinely happy on a long term basis. Mihaly csikszentmihalyi well known psychologist for his international best seller “Flow – The psychology of optimal experience” has nicely explained this paradox in following words - “Despite the fact that we are now healthier and grow to be older despite the fact that even the least affluent among us are surrounded by material luxuries undreamed of even a few decades ago (there were few bathrooms in the palace of the Sun King, chairs were rare even in the richest medieval houses, and no Roman emperor could turn on a TV set when he was bored), and regardless of all the stupendous scientific knowledge we can summon at will, people often end up feeling that their lives have been wasted, that instead of being filled with happiness their years were spent in anxiety and boredom1”.